Fully synthetic phosphorylated Tau181, Tau217, and Tau231 calibrators for Alzheimer’s disease diagnosis - Xinyu Li; Huimei Zeng; Pradeepraj Durairaj; Weihuan Wen; Tianpeng Li; Yanru Zhao; Yang Liu; Xue Liu; Lingpeng Zhan; Lang Rao; Wen Yuan; Tengfei Guo; et al. (Frontiers in Aging Neuroscience, 2024)
BackgroundThe calibrator in immunoassay plays an essential role in diagnosing Alzheimer’s disease (AD). Presently, the most well-studied biomarkers for AD diagnosis are three phosphorylated Tau (p-Tau): p-Tau231, p-Tau217, and p-Tau181. Glycogen synthase-3beta (GSK3β)-phosphorated Tau-441 is the most commonly used calibrator for p-Tau immunoassays. However, the batch-to-batch inconsistency issue of the commonly used GSK3β-phosphorylated Tau-441 limits its clinical application.MethodsWe have successfully generated and characterized 61 Tau monoclonal antibodies (mAbs) with distinct epitopes by using the hybridoma technique and employed them as capture or detection antibodies for p-Tau immunoassays. Through chemical synthesis, we synthesized calibrators, which are three peptides including capture and detection antibody epitopes, for application in immunoassays that detect p-Tau231, p-Tau217, and p-Tau181. The novel calibrators were applied to Enzyme-linked immunosorbent assay (ELISA) and Single-molecule array (Simoa) platforms to validate their applicability and establish a range of p-Tau immunoassays.ResultsBy employing the hybridoma technique, 49 mAbs recognizing Tau (1–22), nine mAbs targeting p-Tau231, one mAb targeting p-Tau217, and two mAbs targeting p-Tau181 were developed. Peptides, including recognition epitopes of capture and detection antibodies, were synthesized. These peptides were used as calibrators to develop 60 immunoassays on the ELISA platform, of which six highly sensitive immunoassays were selected and applied to the ultra-sensitive Simoa platform. Remarkably, the LODs were 2.5, 2.4, 31.1, 32.9, 46.9, and 52.1 pg/ml, respectively.ConclusionThree novel p-Tau calibrators were successfully generated and validated, which solved the batch-to-batch inconsistency issue of GSK3β-phosphorylated Tau-441. The novel calibrators exhibit the potential to promote the standardization of clinical AD diagnostic calibrators. Furthermore, we established a series of highly sensitive and specific immunoassays on the Simoa platform based on novel calibrators, which moved a steady step forward in p-Tau immunoassay application for AD diagnosis.